2023
DOI: 10.3390/su15107988
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Framework to Explore Corporate Ability and Corporate Social Responsibility Association’s Influence on Consumer Responses in the Banking Sector

Abstract: In response to the rising attention being given to corporate social responsibility (CSR) activities in the marketplace, this study aims to explain how corporate ability in terms of CSR initiatives influences consumer attitudinal (trust) and behavioral (purchase intention and word of mouth (WOM)) outcomes in the context of the Indian retail banking industry. The data for the study were taken from banking customers through a survey administered in the bank branch during working hours. Non-probabilistic convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…In the insurance sector, several studies have confirmed the positive relationship between CSR practices and company performance, which improves brand image, customer satisfaction, and employee performance. The results of this research are consistent with the findings of Le [24], which demonstrated that CSR positively impacts customer loyalty, and CSR product awareness and corporate image directly influence product uptake [83][84][85]. The positive impact of CSR on corporate branding has also been confirmed by Soleimani et al [86].…”
Section: Discussionsupporting
confidence: 90%
“…In the insurance sector, several studies have confirmed the positive relationship between CSR practices and company performance, which improves brand image, customer satisfaction, and employee performance. The results of this research are consistent with the findings of Le [24], which demonstrated that CSR positively impacts customer loyalty, and CSR product awareness and corporate image directly influence product uptake [83][84][85]. The positive impact of CSR on corporate branding has also been confirmed by Soleimani et al [86].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, CSR authenticity may be defined as the honesty and genuineness of an organization's CSR activities. The notion of corporate social responsibility has attained international consideration (Fatma & Khan, 2023). In September 2015, the United States produced seventeen sustainable development objectives with consensus that explicitly focused on the ecological and social elements and incorporated CSR (Yasin, Huseynova, & Atif, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have emphasized the value of CSR attributes (Liu & Jung, 2021), CSR fit (Kim, Park, & Kim, 2020;Liu & Jung, 2021), and CSR impact (Ferreira & Real de Oliveira, 2014;Liu & Jung, 2021). Furthermore, while the corporate social responsibility concept is attaining value in businesses and companies by investing further in CSR (Fatma & Khan, 2023). Understanding the elements that affect the authenticity of CSR is one of the literature's major gaps.…”
Section: Introductionmentioning
confidence: 99%
“…CSR authenticity may be defined as the degree to which CSRrelated actions conducted by corporations are real and sincere. The notion of corporate social responsibility (CSR) has garnered significant international interest (Fatma & Khan, 2023). In September 2015, United States formulated a set of seventeen sustainable development objectives that were widely agreed upon and specifically targeted environmental and social dimensions, while also including the concept of corporate social responsibility (Yasin, Huseynova, & Atif, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…While existing researches have highlighted the significance of various aspects, including CSR attributes (Liu & Jung, 2021), CSR fit (Liu & Jung, 2021), CSR impact (Liu & Jung, 2021) CSR competencies, and CSR dimensions (Tsang, Hu, & Li, 2020), environmental CSR, economic CSR (Shim, Moon, Lee, & Chung, 2021), and social CSR (Ferreira & Real de Oliveira, 2014) in many countries by focusing on other various sectors banking, electronical (Huifang & Jin-Sup, 2021) and pharmaceutical industries. Moreover, although the concept of CSR is getting more value in businesses and companies are investing more in CSR (Fatma & Khan, 2023). There is a considerable gap in the existing body of research when it comes to comprehending the elements that influence CSR authenticity (Alhouti et al, 2016) initiatives in developing countries like Pakistan with limited resources and infrastructure, a lack of regulations and standards, and specific challenges related to labor, environmental, and social (Bux, Zhang, & Ahmad, 2020).…”
Section: Introductionmentioning
confidence: 99%